(untitled) (Ukrainian Journal of Ophthalmology, 2025)
Aim: clinical evaluation of the effectiveness of various lasers in treating acute and chronic central serous chorioretinopathy. Methods. The study involved 50 patients (53 eyes) with central serous chorioretinopathy (CSCR): 32 (60.4%) with the acute form and 18 (39.6%) with the chronic form. Patients were divided into three groups based on treatment and the leakage point’s (LP) location. Group 1; 19 patients (19 eyes) received focal laser coagulation. Group 2 included 24 patients (24 eyes) who underwent subthreshold micropulse laser treatment (SMLT) for retinal neuroepithelial detachment. Group 3; 7 patients (10 eyes) with chronic disease underwent focal coagulation combined with SMLT, with LP confirmed via fluorescein angiography (FA). The observation lasted 6 months. Results. At the 4-week follow-up, Group 1’s best corrected visual acuity (BCVA) improved by 60.2% to 0.75±0.01, with central retinal thickness (CRT) decreasing by 72.8% to 257.2±13.1 µm (p<0.05). Group 2 experienced a 30% BCVA improvement to 0.5±0.02, and a 32.1% CRT reduction to 266.6±10.3 µm (p<0.05). Group 3 showed a 26.5% BCVA increase to 0.35±0.01, with CRT decreasing by 27.3% to 280.6±14.5 µm (p<0.05). Conclusions. When the leakage point (LP) is located in the subfoveal region, in cases of the chronic form of the disease with large-area diffuse hyperfluorescence, in situations where the filtration point is not detected by fluorescein angiography (FA), and in cases of disease recurrence, subthreshold micropulse laser treatment, the use of subthreshold micropulse mode laser devices with a yellow wavelength (577 nm) is considered a safe and effective therapeutic method.